Chlorhexidine hexametaphosphate as a wound care material coating: antimicrobial efficacy, toxicity and effect on healing - Barbour, Michele E; Maddocks, Sarah E; Grady, Helena J; Roper, James A; Bass, Mark D; Collins, Andrew M; Dommett, Rachel M; Saunders, Margaret (Nanomedicine (London, England), 2016)
In this study, chlorhexidine hexametaphosphate (CHX-HMP) is investigated as a persistent antimicrobial coating for wound care materials. CHX-HMP was used as a wound care material coating and compared with chlorhexidine digluconate materials with respect to antimicrobial efficacy, toxicity and wound closure. Antimicrobial efficacy at day 1, 3 and 7 was observed with experimental and commercial materials. CHX-HMP coated materials had less toxic effect on human placental cells than commercial chlorhexidine dressings. CHX-HMP in pluronic gel did not delay healing but reduced wound colonization by . CHX-HMP could become a useful component of wound care materials with sustained antimicrobial efficacy, lower toxicity than chlorhexidine digluconate materials, and reduction in wound colonization without affecting closure.